Prevention of Postoperative Thromboembolism in Sweden – The Development of Practice During Five Years - Bergqvist, David (Thrombosis and Haemostasis, 1985)
All climes in Sweden (223) dealing with general, urologie, orthopaedic, and gynaecologic surgery were sent a questionnaire concerning their policy about prophylaxis against postoperative thromboembolism in 1982. The praxis was also compared with that obtained in a similar survey in 1977. 96% replied. 91% used some sort of specific prophylaxis which is significantly more than in 1977. Also a significantly larger number of patients were operated on with prophylaxis than in 1977 (25 vs 19%). The dominating methods were dextran 70 and low-dose heparin. Compared with 1977 peroral anticoagulation, low-dose heparin and mechanical methods had decreased significantly, low-dose heparin in combination with dihydroergotamine increased significantly and dextran showed an unchanged use.
Keywords: Thromboembolism; Prophylaxis; Survey